Effect of the Perspectives of intellectual disabilities teachers towards the absence of job security and its impact in day care centers - Al-Sihli, Ebtisam Saeed; Khares, Walaa Abdullah (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to identify the perceptions of intellectual education teachers about the lack of job security in day care centers in the Medina region. Disclosure of its effects, and proposals that may contribute to improving the level of job security in day-care centers. To achieve the objectives of the study, the qualitative approach was used, and the interview was relied on as a study tool to collect qualitative data, from the sample that was selected for the study, which was represented in (10) intellectual education teachers working in daycare centers in the Medina region. Based on the analysis of the collected data, the study found in its results that there is a deficiency in achieving job security in day care centers in the Medina region, and that there is a positive relationship between job security and the quality of performance, where the higher the level of job security, the higher the quality of performance and vice versa, and one of the consequences of the absence of job security is the negative impact on the quality of educational outcomes, and it was also concluded that the impact of the absence of job security is not limited to the quality of performance, and the quality of Educational outcomes, but also negatively affects the psychological level of the education teacher.